Assessment of the burdens of residential neighbourhood crime - Olajidei, Sunday Emmanuel; Mohd Diah, Mohd Lizam; Akinbola, Kazeem Bolayemi (Open Access Publishing Group, 2017)
The responses of government, public, researchers and professionals alike could have been boosted in need to tenaciously tackle residential neighborhood crime if there were enough research and publication on the diverse consequences of residential neighborhood crime. The main objective of this article is to critically evaluate the consequences of residential neighborhood crime. The research finding revealed a triangular nature of the consequences in that it burdens on the property and its environs; on government and its agencies and thirdly on the residents. This study believes that tackling residential neighborhood crime portends some benefits like the removal of fear of crime which will inferably boost residents’ health status towards efficiency of labour, boost housing investment, increase government revenue from property tax and in turn reduce public spending on crime control. All these efforts would translate to environmental sustainability.